Quantitative Approaches in Decision Theory for Enhancing Risk Assessment Strategies - Ismail, Mohammed Nuther; Kallow, Sabah M.; Gati, Kamal Hameed; Al-Bayati, Husam Najm Abbood; Butsenko, Yurij (Journal of Ecohumanism, 2024)
Background: Conventional risk assessment methods frequently need to consider the intricacy and fluidity of modern decision-making environments adequately. Integrating decision theory provides a robust framework for assessing uncertainties and their impact on decision results. Objective: This research investigates the practical application of quantitative approaches in decision theory to enhance risk assessment processes. The ultimate goal is facilitating more informed and rational decision-making in diverse circumstances. Method: This work utilizes a thorough literature analysis and mathematical modeling to analyze current decision theory approaches, specifically emphasizing their quantitative characteristics and suitability for risk assessment. The primary factors for assessment are precision, effectiveness, and versatility in accommodating various risk scenarios. Results: The findings demonstrate that applying quantitative decision theory techniques, such as Bayesian probability, decision trees, and Monte Carlo simulations, significantly improves the accuracy and dependability of risk assessments. These strategies provide a systematic approach to integrating uncertainty and variability into the decision-making process, resulting in a more precise understanding of potential risks and outcomes. Conclusion: Quantitative approaches integrated into decision theory are potent tools for enhancing risk assessment methodologies. Enhancing comprehension of uncertainties and their prospective consequences empowers decision-makers to negotiate intricate situations with greater efficiency, resulting in more sturdy and adaptable decision outcomes. This study highlights the importance of using quantitative decision theory to improve risk assessment processes and paves the way for future investigations into their practical uses.